2020
DOI: 10.3928/1081597x-20200730-03
|View full text |Cite
|
Sign up to set email alerts
|

Early Corneal and Epithelial Remodeling Differences Identified by OCT Imaging and Artificial Intelligence Between Two Transepithelial PRK Platforms

Abstract: PURPOSE: To analyze corneal and epithelial remodeling differences between SmartSurfACE reverse transepithelial PRK (SCHWIND eye-tech-solutions) and Streamlight (Alcon Laboratories, Inc) transepithelial PRK procedure using optical coherence tomography (OCT) and artificial intelligence (AI). METHODS: This was a prospective, interventional, and longitudinal study. A contralateral eye study was conducted in which one eye was assigned to the SmartSurfACE gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…There is no universally accepted staging system for KC; however, significant advances in artificial intelligence in recent years can help identify the proper indications for surgery. 14 Pachymetric 41 and tomographic indices 42 integrate with biomechanical evaluation of cornea, 43 anterior corneal higher order aberrations (HOAs), 44 and ultra-high-resolution Optical Coherence Tomography (OCT) 45 not only use preoperatively, but also for postoperative (epithelial remodeling 46 and anterior stromal demarcation) management. 47 Furthermore, regarding genetic aspects 3 , 7 and metabolic imbalance of the disease, 48 recent reviews considered that micronutrients such as metal ions, vitamins, hormones, antioxidants, oral riboflavin, and Essential Fatty Acids, can deeply influence KC initiation and progression, particularly in the early stages of KC.…”
Section: Resultsmentioning
confidence: 99%
“…There is no universally accepted staging system for KC; however, significant advances in artificial intelligence in recent years can help identify the proper indications for surgery. 14 Pachymetric 41 and tomographic indices 42 integrate with biomechanical evaluation of cornea, 43 anterior corneal higher order aberrations (HOAs), 44 and ultra-high-resolution Optical Coherence Tomography (OCT) 45 not only use preoperatively, but also for postoperative (epithelial remodeling 46 and anterior stromal demarcation) management. 47 Furthermore, regarding genetic aspects 3 , 7 and metabolic imbalance of the disease, 48 recent reviews considered that micronutrients such as metal ions, vitamins, hormones, antioxidants, oral riboflavin, and Essential Fatty Acids, can deeply influence KC initiation and progression, particularly in the early stages of KC.…”
Section: Resultsmentioning
confidence: 99%
“…21 The 3D distribution of epithelium quantified with epithelial Zernike indices and total corneal thickness were also computed from the exported comma-separated value files of MS-39. 22 From Corvis-ST, the Corvis biomechanical index (CBI), total biomechanical index (TBI) and Belin-Ambrósio overall deviation index (BAD-D) were analyzed. Patient demographics included age, sphere, cylinder, and uncorrected and corrected distance visual acuities.…”
Section: Methodsmentioning
confidence: 99%
“…Laser platforms and surgical techniques can also alter this epithelial thickness change. Shetty et al [ 157 ] showed higher degrees of epithelial thickness distortion in the Streamlight group than in the SmartSurfACE one. Lu et al [ 158 ] investigated the effect of mitomycin-C (MMC) in epithelial remodeling.…”
Section: Refractive Surgerymentioning
confidence: 99%